Jabatan Pengairan dan Saliran Daerah Muar / Nurkamelia Syuhada Jamal - Jamal, Nurkamelia Syuhada (UITM Cawangan Johor Kampus Pasir Gudang, 2018)
Industrial training is an obligation for every student in Faculty of Civil Engineering for Diploma in Civil Engineering as a condition of the award of diploma at the end of this course. The aims of industrial training are to provide students with exposure and give experience on the real situation in the field of construction management as an early preparation for the students before stepping into the workplace. Exposure to real-time working situations in industrial training for industrial training student is able to give them a glimpse of the difference between in workplace and the situation during learning session at university. Industrial training is very useful for students to gain new experiences and it can also make the student personality to become good and be more discipline in time and circumstance. During the time for this government department in Muar District Irrigation and Drainage Irrigation and Drainage Department, industrial training student were able to go through a whole range of new experiences in their life especially in the workplace. While undergoing industrial training, the most important aspect that can get is industrial training can give students the opportunity to know the true nature of work. In addition, industrial training can also enhance the knowledge of students and open the mind of students to think how a product is produced. In this company, there are various activities that can carry out and not only focusing on the construction sites but also the history of Johor, hydrology and office management. All the information get during this industrial training, it may help to improve industrial training student academic understanding in scope of civil engineering